Punishment and incarceration a global perspective - Deflem, Mathieu (Bingley, U.K. : Emerald, 2014)
This volume in the series Sociology of crime, law, and deviance deals with aspects of punishment, including sentencing, incarceration, and prison conditions, in a variety of settings at local, national, and/or regional levels. The book brings together some 14 scholars to contribute their respective chapters, each of the authors drawn from various parts of the world, thus ensuring a global perspective. The chapters in this volume address specific aspects of punishment, prisons, and incarceration based on the authors unique specialty and setting. The focus is explicitly comparative, analyzing punishment in different national and regional settings, and thus seeks to offer a global orientation. Both thematically and regionally diverse within the province of social and behavioral studies devoted to the study of punishment and incarceration, the chapters in this volume are also diverse in terms of theoretical approach and methodological orientation.
Legitimacy and punitiveness : the role of judicial actors in Italian penality / Zelia Gallo -- Juvenile justice and incarceration in Turkey / Serkan Tasgin -- The trajectory of penal markets in a period of austerity : the case of England and Wales / Mary S. Corcoran -- 'Ceci N'est Pas Une Fouille A Corps' : the denial of strip searches in Belgian prisons / Tom Daems -- Stuck : conditions of Canadian confinement / Rose Ricciardelli, Hayley Crichton, Lisa Adams -- Women prisoners : theory and reality in Mexico / Elena Azaola -- Three waves of American prison development, 1790-1920 / Ashley T. Rubin -- Native American incarceration : a neglected problem? / Roy F. Janisch -- Continued imprisonment of terminally ill prisoners in the United States : an international human rights perspective / Aleksandr Khechumyan -- Sentencing and incarceration in a democratic South Africa / Willem F.M. Luyt -- Punishment and incarceration in Japan : a net-widening of crime control and a new priority system of prosecution / Shinichi Ishizuka -- Gender and imprisonment in Hong Kong / Maggy Lee, K. Joe Laidler.
Print version record
Keywords: Law -- Criminal Law -- General; Social Science -- Criminology; Penology & punishment; Prisons; Crime & criminology; Punishment; Imprisonment